How are you? - Aiman Azlan; Aiman Amri (Iman Publication Sdn Bhd, 2019)
A Friend asks, "How Are You?" You want to say, "I'm fine", but you know that is untrue. You are in pain, but you don't know how to express it. A friend says, "I'm fine", but you know there is something more beyond those words. You notice something is not right, but you don't know what to do. You want to understand and help but you don't know where and how to start. Stress, Anxiety, and Depression are 3 of the most common and emotional challanges that people are struggling with. No one should be left to face the struggle alone and no one should. How Are You?, written by Assistant Psychologist Aiman Amri and Youth Motivator Aiman Azlan, explores the topic of Stress, Anxiety and Depression; from how survivor can cope with them to how friends and family members can understand these human problems better so that they may be compassionate and considerate towards those who struggle in silence. They are no longer alone.